Normalized Differenced Vegetation Index (NDVI) of riparian areas with and without beaver damming within wildfire perimeters in Western US - Emily Fairfax (PANGAEA, 2019)
These data are from 5 wildfires that burned in recent decades in the western United States. The data is NDVI along creeks within the wildfire perimeters in areas that do and do not have beaver damming. Data is in columns with pre, during, and post fire NDVI, distance along creek in meters, and presence of beavers (0 = beavers, blank = no beavers) For more information please contact Emily Fairfax.